2018
DOI: 10.4149/bll_2018_131
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and cost of burns in emergency department during Syrian civil war

Abstract: BACKGROUND: We aimed to emphasize the importance of regional hospitals' capacities and emergency services for burn patients in war and disaster situations, in addition to assessing the costs and clinical situations of seriously burned patients who have come to the emergency service due to the bomb and heater burst during the Syrian civil war. METHODS: In this study, we analyzed these 217 burn patients and analyzed these patients' data for retrospective analysis. RESULTS: Burn patients were more often seen duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The wound healing time, burn severity, and hospitalization length and grafting were important contributors to the medical burden for burn patients. 30 This study found that patients receiving emergency conservative debridement had a significant lower mean LOS than that of patients in the dressing group. However, no significant difference of mean in-hospital cost per 1% TBSA between the 2 groups was observed.…”
Section: Discussionmentioning
confidence: 63%
“…The wound healing time, burn severity, and hospitalization length and grafting were important contributors to the medical burden for burn patients. 30 This study found that patients receiving emergency conservative debridement had a significant lower mean LOS than that of patients in the dressing group. However, no significant difference of mean in-hospital cost per 1% TBSA between the 2 groups was observed.…”
Section: Discussionmentioning
confidence: 63%
“…Most of the previous studies only focused on war-related injuries in war-heated areas (8),or on Syrian patients referred to a hospital in the neighboring countries (9,10). only one study focused on day-to-day burn injuries in Syria which took place in Aleppo, Al-Kindi Hospital between 1990 and 1992 on 492 bums patients (11).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies specifically examined noncombat burn injuries among children in Iran, Iraq, Afghanistan, and Syria who were treated as part of humanitarian care provided by the U.S. military (Edwards et al, 2014;Karimi et al, 2012;Kuvandik, Ucar, and Karakus, 2018;Wilson et al, 2013) and U.S. military partners (Arul et al, 2012). In a case review of trauma admissions to a U.S. combat support hospital in Afghanistan, burns represented the most common noncombat injury among pediatric patients and required the most operative procedures (Arul et al, 2012).…”
Section: Incidence and Prevalence Of Burn Injuriesmentioning
confidence: 99%